Pengaruh Variasi Karbon Aktif dan Waktu Tahan Terhadap Kekerasan Material JIS G-3123 Menggunakan Metode Pack Carburizing - Rahma Rei Sakura; Suheni Suheni; Dani Darojat Iskandar (Universitas Muhammadiyah Sidoarjo, 2017)
Improvement of mechanical feature in metals are necessary for industrial development. In industries, it requires the mechanical features, such as frictional strength and good wear resistance. Carburizing is a heat treatment process that produces toughness surface in the presence of carbon-bearing material. The carburizing process of JIS G-3123 steel was performed by Pack Carburizing method with divergent variation of activated carbon weigh(s) 125 grams, 250 grams, and 400 grams and selected holding time in range of 30 minutes, 45 minutes, and 60 minutes. In the result, it was obtained 463.550 kg / mm2 for the highest value of toughness with the weight of 400 gr activated carbon and holding time of 30 minutes. Therefore, it indicated that the higher weight of activated carbon in the carburizing process, the material hardness value will be higher as well, with the lowest holding time.